ПРЕДВАРИТЕЛЬНАЯ ОЦЕНКА ТАКСОНОМИЧЕСКОГО СОСТАВА ФАУНЫ МОЛЛЮСКОВ КАЗАХСТАНА (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In the present work results of revision of the faunistic data on the molluscs of Kazakhstan taken from the literature are resulted, in view of advanced achievements of recent systematics. The list of all taxa from classes up to genera with the indication of quantity of species in each genus is resulted. It is established, that the fauna of Kazakhstan includes 496 species of the molluscs concerning to 2 classes, 42 families and 121 genera, and to Gastropoda - 385 species from 92 genera of 33 families, and to Bivalvia - 111 species from 29 genera of 9 families concern.